Effectiveness of the NETES (Niat Engsun Tuntas cEgah Stunting/My Intention to Prevent Stunting Completely) Program to Prevent Stunting - Tutiek Herlina; Nurweningtyas Wisnu; Dian Maheru Robbi; Yuanita Sinar Yuliati; Rahma Anindita (Knowledge Dynamics, 2024)
Background: Stunting was described as a toddler whose height was lower than the standard height for children of the same age, which was a characteristic that indicates repeated and long-term nutritional problems. The negative impact in the long term was decreased cognitive ability and learning achievement, body immunity, and a high risk of diabetes, obesity, heart and blood vessel disease, cancer, stroke, and disability in old age. The prevalence of stunting in Plaosan Subdistrict increased from 2021 by 7.54%, in 2022 by 7.91% and in 2023 by 8.52%. The